The relationship of self-esteem, perceived social support and help-seeking intentions among university students in Malaysia - Tan, Lian Jia (2024)
The transformation of the world in this era of globalization evokes a stressful and anxiety-provoking time for society, drawing people's attention to the importance of having active coping strategies such as help seeking in response to the challenge. However, global statistics report an alarming issue of low help-seeking intentions, and Malaysia is no exception. Therefore, the present study examined the relationships between self-esteem, perceived social support, and help-seeking intentions among university students in Malaysia. Three instruments were used to measure the respective constructs, including the 10-Item Rosenberg Self-Esteem Scale, the 12-Item Multidimensional Perceived Social Support scale, and the 2-Item General Help-Seeking Questionnaire. A cross-sectional survey design with quantitative methodology was employed, utilizing a purposive sampling method to recruit Malaysian university students aged between 18 to 24 years and currently pursuing studies in Malaysia. A total of 188 Malaysian university students aged between 18 to 24 years (M = 22.053; SD = 1.068), with the majority of female (n = 156; 82.98%), participated in the present research by completing the online self-report questionnaire. The results indicate that university students in Malaysia have high self-esteem, medium perceived social support, and high help-seeking intentions. There was no significant relationship between self-esteem and help-seeking intentions, nor did self-esteem significantly predict help-seeking intentions. In contrast, a positive relationship was found between perceived social support and help-seeking intentions, with perceived social support positively predicting help-seeking intentions. These findings not only casting a fresh perspective on the existing literature about help-seeking intentions in the Malaysian context but also provide empirical support for mental health care providers in developing evidence-based programs related to help-seeking intentions.